Association between the skeletal muscle-to-visceral fat ratio and kidney stones: a cross-sectional study - Du, Yuan-Zhuo; Yang, Jia-Qing; Tang, Jian; Zhang, Chi-Teng; Liu, Yi-Fu (Frontiers in Nutrition, 2025)
ObjectivePrior research has suggested links between skeletal muscle mass and visceral fat volume with kidney stone formation. However, the link between the skeletal muscle-to-visceral fat ratio (SVR) and kidney stone risk remains to be clarified. This study aims to explore the relationship between SVR and the risk of kidney stones, analyzing data from the National Health and Nutrition Examination Survey (NHANES).MethodsThe research encompassed 8,522 individuals from NHANES surveys from 2011 to 2018. Kidney stones were diagnosed through a standardized questionnaire, and SVR was calculated using dual-energy X-ray absorptiometry (DXA). Participants were grouped into quartiles based on their SVR. All data underwent weighting according to official guidelines. Logistic regression models assessed the correlation between SVR and kidney stone incidence, and subgroup analysis was employed to investigate its stability.ResultsAmong the participants, 675 individuals, representing 8.73%, received a diagnosis of kidney stones, with an average age of 39.29 years (±0.28). Findings indicate that lower SVR correlates with increased kidney stone risk. Within the comprehensively adjusted multivariate model, compared to the lowest SVR quartile, the second, third, and fourth quartiles demonstrated significantly reduced risks, with ORs of 0.63 (95% CI = 0.47–0.84), 0.57 (95% CI = 0.42–0.79), and 0.39 (95% CI = 0.25–0.61), respectively. Restricted cubic spline (RCS) regression models demonstrated a non-linear relationship between SVR and kidney stone risk. The subgroup analysis demonstrated no significant differences in weighted associations across subgroups (interaction p-value > 0.05), except for BMI, which had a significant interaction (interaction p-value < 0.05).ConclusionThe findings underscore that lower SVR correlates with increased kidney stone risk, a relationship that remains consistent across most demographics.